Review – Potentials and limitations of utilising brewer's spent grain as a protein source in aquaculture feeds. (10th July 2022) - Karlsen, Freja; Skov, Peter V.
Abstract: On a worldwide basis, aquaculture is among the most important food-producing industries. The steadily growing population has led to an increased demand for aquaculture products, which in turns has intensified the farming of aquatic species along with aquafeed production. Fishmeal and soybean meal represent two of the most widely used protein sources in aquafeeds. Increasing demands and costs have fostered a need for supplementing fishmeal and soybean meal with sustainable alternatives in the coming years. Brewer's spent grain (BSG) is the major by-product generated in beer brewing. With a relatively high protein content, low market price and stable annual availability BSG represents a potential protein source for aquaculture feeds. However, in its untreated form BSG contains high levels of anti-nutritional factors (ANFs) such as lignin and fibre which are known to reduce digestive performance in fish. Furthermore, BSG appears to be perishable under inappropriate storage conditions due to its high moisture content. Therefore, the main objective of this review was to compile an overview of different methods that may help facilitate the implementation of BSG in aquafeed. Before BSG may be utilised as a protein source, it must undergo refinement to remove lignocellulosic material. Here, we focus on two general approaches commonly used: a fractionation-and a conversion-based method. The fractionation-based approach relies on chemical extractions to separate BSG into its constituents, thereby removing the ANFs from the protein component. The conversion-based approach aims to transform ANFs into digestible substances by applying a combination of chemical, biological and enzymatic treatments. Application of appropriate preservation methods can help prevent microbial colonisation of BSG. Three different preservation methods were compared including freeze-drying, oven-drying and lactic acid bacteria (LAB) treatment. Of these, LAB treatment appears to be the most favourable with respect to energy-costs and potential health benefits. At present, BSG has not found any practical use in aquafeed production. However, the collection of methods presented in this review may provide a basis for incorporating BSG in aquafeeds and highlight possible future directions for realising this aim. Highlights: Applying alternative protein sources in aquafeed may enhance sustainable development. Brewer's spent grain constitutes a potential, unrealised protein source for fish feed. Brewer's spent grain has low nutritional quality due to high levels of lignocellulose. Protein extraction may be a useful method for separating proteins from lignocellulose. Delignification and fibre hydrolysis may be useable in lignocellulose conversion.